Land tenure and property rights, and the impacts on adoption of climate-smart practices among smallholder farmers in selected agro-ecologies in Nigeria - Mojisola O. Kehinde; Adebayo M. Shittu; Maria G. Ogunnaike; Funminiyi P. Oyawole; Oluwakemi E. Fapojuwo (Bio-based and Applied Economics, 2022)
This study investigates the effects of land tenure and property rights (LTPRs) on smallholder farmers’ adoption of climate-smart practices (CSPs) among cereal farming households in Nigeria. The data were collected from maize and rice farmers in a Nation-wide Farm Household Survey conducted across the six geopolitical zones in Nigeria. Data collected were analysed within the framework of Multivariate Probit to determine the factors that facilitate and/or impede the adoption of CSPs. The results showed that the adoption of CSPs considered in this study – agroforestry, zero/minimum tillage, farmyard manure, crop rotation and residue retention - were generally low. Empirical analysis showed that farmers with transfer right were more likely to adopt farmyard manure, crop rotation and residue retention while the likelihood of adopting agroforestry reduced with having transfer right. The coefficient of de jure secure increased the likelihood of adopting zero/minimum tillage while the coefficient of control right increased the likelihood of adopting agroforestry. Again, we found that the adoption of zero/minimum tillage reduced with control and transfer rights. The study also contributes to the existing literature on adoption by recognizing the interdependence between different climate-smart practices as well as jointly analyse the decision to adopt multiple CSPs. The study therefore, suggests that governments, in whom the responsibility for land use policy reform lies, review the existing framework to ensure a prompt, fair, and efficient land tenure system.